such that
Gives,
and,
Then evaluate ,
This problem is original.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is given that f ( x ) = a x 3 + b x 2 + c x + d , where a , b , c , d ∈ N . It is also given that:
⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ f ( 1 ) + f ( 2 ) f ( 2 ) + f ( 3 ) f ( 3 ) + f ( 4 ) f ( 5 ) = 9 a + 5 b + 3 c + 2 d = 3 5 a + 1 3 b + 5 c + 2 d = 9 1 a + 2 5 b + 7 c + 2 d = 1 2 5 a + 2 5 b + 5 c + d = 5 1 = 1 1 1 = 2 1 3 = 2 3 1 . . . ( 1 ) . . . ( 2 ) . . . ( 3 ) . . . ( 4 )
From (4), for a , b , c , d ∈ N , a can only be 1 because if a = 2 and the minimum value of f ( 5 ) = 2 5 0 + 2 5 + 5 + 1 = 2 8 1 > 2 3 1 , when b = c = d = 1 . Substituting a = 1 in the rest of the equations, we have:
⎩ ⎪ ⎨ ⎪ ⎧ ( 1 ) : ( 2 ) : ( 3 ) : 5 b + 3 c + 2 d 1 3 b + 5 c + 2 d 2 5 b + 7 c + 2 d = 4 2 = 7 6 = 1 2 2 . . . ( 1 a ) . . . ( 2 a ) . . . ( 3 a )
( 2 a ) − ( 3 a ) : ( 3 a ) − ( 2 a ) : ( 6 ) − ( 5 ) : ( 5 ) : ( 1 a ) : 8 b + 2 c = 3 4 1 2 b + 2 c = 4 6 2 b = 6 4 ( 3 ) + c = 1 7 5 ( 3 ) + 3 ( 5 ) + 2 d = 4 2 ⇒ 4 b + c = 1 7 ⇒ 6 b + c = 2 3 ⇒ b = 3 ⇒ c = 5 ⇒ d = 6 . . . ( 5 ) . . . ( 6 )
⇒ ( a + b + c + d ) a b c d = ( 1 + 3 + 5 + 6 ) ( 1 × 3 × 5 × 6 ) = 1 5 × 9 0 = 1 3 5 0
Previous solution using matrix calculations.
⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ f ( 1 ) = a + b + c + d f ( 2 ) = 8 a + 4 b + 2 c + d f ( 3 ) = 2 7 a + 9 b + 3 c + d f ( 4 ) = 6 4 a + 1 6 b + 4 c + d f ( 5 ) = 1 2 5 a + 2 5 b + 5 c + d
⇒ ⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ f ( 1 ) + f ( 2 ) f ( 2 ) + f ( 3 ) f ( 3 ) + f ( 4 ) f ( 5 ) = 9 a + 5 b + 3 c + 2 d = 3 5 a + 1 3 b + 5 c + 2 d = 9 1 a + 2 5 b + 7 c + 2 d = 1 2 5 a + 2 5 b + 5 c + 1 d = 5 1 = 1 1 1 = 2 1 3 = 2 3 1
⇒ ⎝ ⎜ ⎜ ⎛ 9 3 5 9 1 1 2 5 5 1 3 2 5 2 5 3 5 7 5 2 2 2 1 ⎠ ⎟ ⎟ ⎞ ⎝ ⎜ ⎜ ⎛ a b c d ⎠ ⎟ ⎟ ⎞ ⎝ ⎜ ⎜ ⎛ a b c d ⎠ ⎟ ⎟ ⎞ = ⎝ ⎜ ⎜ ⎛ 5 1 1 1 1 2 1 3 2 3 1 ⎠ ⎟ ⎟ ⎞ = ⎝ ⎜ ⎜ ⎛ 9 3 5 9 1 1 2 5 5 1 3 2 5 2 5 3 5 7 5 2 2 2 1 ⎠ ⎟ ⎟ ⎞ − 1 ⎝ ⎜ ⎜ ⎛ 5 1 1 1 1 2 1 3 2 3 1 ⎠ ⎟ ⎟ ⎞ = 9 0 1 ⎝ ⎜ ⎜ ⎛ − 7 7 4 − 2 5 4 2 7 0 2 0 − 1 9 5 5 6 4 − 4 5 0 − 1 7 1 5 0 − 3 7 9 2 6 9 7 − 6 0 1 3 6 − 9 0 ⎠ ⎟ ⎟ ⎞ ⎝ ⎜ ⎜ ⎛ 5 1 1 1 1 2 1 3 2 3 1 ⎠ ⎟ ⎟ ⎞ = ⎝ ⎜ ⎜ ⎛ 1 3 5 6 ⎠ ⎟ ⎟ ⎞
⇒ ( a + b + c + d ) a b c d = 1 5 × 9 0 = 1 3 5 0